Sistem Intensifikasi Tanaman Padi SRI Melalui Pemanfaatan Mikroorganisme Lokal Dalam Pembuatan Kompos Dapat Meningkatkan Populasi Mikroba Tanah (Studi Kasus Di Desa Sidodadi Kabupaten Deli Serdang) - ekamaida ekamaida (Agrium, 2018)
System of Rice Intensification (SRI) by a Local Microorganisme Usage (MOL) in Producing the Compost Fertilizer (Case Study at Desa Sidodadi Kabupaten Deli Serdang) is expected to maintain the fertile of land, improve land microbia population and to preserve the environment at once capable to maintain or improve land productivity. The agriculture system with SRI is applied by using organic material such as fruif waste whis is fermented to produced MOL used as decomposer in composing proges. This reseach studied microbia population where an organik agricaltural system (SRI) has been applied. The reseach was comparedl of mikroba population soil also whith how effect SRI aplication between chemical fertilizer  for the managemental in Sidodadi village.Using compost MOL at SRI improved microbia  population soil by the result of soil analysis either chemically and biologically the uses of MOL compost is far better compared for environmental the uses of an-organic fertilizer. The SRI pattern practiced at Desa Sidodadi was an agricultural work  environmentally friendly using organic fertilizer as source of nutrients improve physical, chemical and biological properties of soil as well in increasing production yield.